ANALISIS KRITERIA DAN SUBKRITERIA PRIORITAS DALAM PENGELOLAAN KELOMPOK TANI DI KABUPATEN PATI MENGGUNAKAN ANALYTICAL HIERARCHY PROCESS - Arieyanti; Wahyudi, Jatmiko (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2023)
The agricultural sector is one of the significant contributors to the regional economy of Pati Regency. However, this sector declined at the growth rate of -0.20% in 2021. One of the reasons is the weak capacity of farmer groups indicated by the main class farmer groups, which only amount to four out of 2,588 groups. Department of Agriculture data shows that the total number of farmer groups is 2,588, divided into 1,612 beginner groups, 830 advanced groups, 78 middle groups, four main groups, and 64 unknown groups. The purpose of the study is to determine the criteria and subcriteria in the management of farmer groups. This quantitative study uses the Analytical Hierarchy Process with 56 respondents. Based on Guidelines for Assessing the Ability of Farmer Groups Classes, farmer group management is influenced by five criteria: planning, developing farmer group leadership, organizing, implementing, and controlling reports. The results showed that the Implementation Criteria prioritize managing farmer groups. Meanwhile, the priority subcriteria in the Implementation Criteria is Business Implementation. One of the implementations is to run the Integrated Farming System (IFS) as part of the Business Implementation subcriteria.